Willingness to pay (WTP) for arsenic-safe drinking water: A case study to understand societal embedding of ECAR technology in rural West Bengal, India. (2022) - Dasgupta, Shyamasree; Roy, Joyashree; Ghosh, Monalisa; Talukder, Jayanta
Abstract: This paper analyzes users' willingness to pay (WTP) for safe drinking water in a resource-poor region in West Bengal, India, with dangerously high groundwater arsenic concentrations. The study was carried out during the installation of an Electro Chemical Arsenic Remediation (ECAR) water treatment plant at the site. Using a contingent valuation method, the study elicits WTP, based on a stratified random sample of 1003 households. Arsenic is invisible and odorless, and related health risks have a prolonged latency period. As a result, awareness about arsenic and the perceived benefits of any arsenic remediation technology are low. In the study area, only 21% of respondents were aware of the danger of high arsenic concentrations in groundwater, however, a large number of the respondents reported irregularity of drinking water supply and a lack of quality assurance. About 64% of the respondents were willing to pay for ECAR-treated safe drinking water. Participants opting for home delivery were willing to pay more than those willing to collect water from the plant. The average WTP was high enough to recover the operational cost of the plant. Households with higher income and educational attainment, more awareness about arsenic contamination, and living in proximity to the plant were willing to pay more than the others. Regular interaction with the community, maintaining transparency, and interacting closely with the local administration created a sense of local ownership for the technology that was found to be crucial for the societal embedding of the technology. Highlights: We analyse willingness to pay (WTP) for safe drinking water in a rural community in India. Only 21% of respondents were aware of the danger of high arsenic concentrations in groundwater. However, 64% were willing to pay for a technological intervention for arsenic remediation. WTP depended on income, arsenic awareness, education, and proximity to the treatment plant. Thus, community engagement and awareness are crucial for societal embedding of technology.